Omental infarction with liquefied necrosis after Roux Y gastric bypass: case report and literature review. Issue 8 (15th August 2020) - Alwatari, Yahya; Gerrish, Ashley; Ayalew, Dawit; Campos, Guilherme M; Salluzzo, Jennifer L
Abstract: Omental infarction is a rare phenomenon that can be idiopathic or secondary to a surgical intervention. Greater omentum division has been advocated to decrease tension at the gastro-jejunal anastomosis during laparoscopic Roux-en-Y gastric bypass (RYGB). We report a case of omental infraction complicated by liquefied infected necrosis presenting 3 weeks after antecolic antegastric RYGB. The patient underwent laparotomy and subtotal omentectomy with a protracted hospital course due to intra-abdominal abscesses, acute kidney injury and small bowel obstruction that were successfully managed non-operatively. We reviewed the available literature on omental infarction after RYGB, focusing on associated symptoms, possible etiology, timing of presentation, management and propose an alternative technique without omental division.